PEMBERDAYAAN MASYARAKAT MELALUI KEGIATAN BUDIDAYA RUMPUT AKAR WANGI (Chrysopogon zizanioides) DI DESA GIRI MADIA, KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT - Alfi, Muhammad Dhia Hasanu; Sulastika, Riyana; Estyana, Ema; Virgota, Arben (Universitas Mataram, 2024)
Vetiver grass (Chrysopogon zizanioides) is a large grass plant and has long and strong roots. Vetiver grass has an important role in minimizing erosion, soil conservation and controlling landslides. The introduction of vetiver grass as a plant to resist erosion and landslides in steep and sandy areas can have a positive impact. However, public knowledge about vetiver grass is still lacking, while the community's need, especially for handling landslides, is very high. The main purpose of planting vetiver grass is to use it as cultivation and from an economic perspective it can help as a new business opportunity for the residents of Giri Madia Village. The method used in writing this article is a qualitative approach with the aim of placing greater emphasis on aspects of an in-depth understanding of the use of vetiver as an opportunity that can be used as a business for the people of Giri Madia Village. The results obtained from this activity are helping residents to increase their knowledge of vetiver grass plants which have economic benefits and can prevent landslides. The existence of demonstration plots in two hamlets in Giri Madia village has resulted in knowledge and awareness regarding landslide disaster mitigation. The workshop is able to provide knowledge about how to prepare seeds, then provide planting media, materials and how to plant and care for vetiver grass so that it can grow and reproduce in order to prevent landslides. The planting was in two hamlets in Giri Madia Village, namely Leong and Leong Jaya Hamlets, because the Village Head recommended that we focus on these two hamlets. The role of the community in Leong Hamlet is active, but their role in maintaining vetiver grass is decreasing day by day because they are busy working. For participation in Leong Jaya Hamlet, it was felt that there was not enough attention paid to caring for the demonstration plots and seedling houses, there were several factors, namely that they had jobs as workers on plantations. So the solution is that the hamlet head must collaborate with the local community for the maintenance and upkeep of the demonstration plot and seedling house.